The Influence Of Vocabulary Mastery On The Ability To Write Explanation Texts Class XI Students of SMA Negeri 3 Depok - Mella Dyah Fitnanda; Bambang Sumadyo; Yayan Sudrajat (PT. Lancar Media Komunikasi, 2023)
The purpose of this study was to determine the effect of vocabulary mastery on the ability to write explanatory texts for class XI students of SMA Negeri 3 Depok. The research method used is the type of data collected in the form of quantitative data using data collection on the ability to write explanatory texts for class XI students of SMA Negeri 3 Depok. Based on the data analysis that has been made by students, it is proven that hypothesis testing with a significant level of 5% is obtained (1.694 > 0.361), there is an effect of vocabulary mastery on the ability to write explanatory texts and the average explanatory text writing skill is 82.1 higher. Keywords: Mastery of Vocabulary, Ability to Write Explanatory Text